Genetic variability, character association and path coefficient analysis in rice (Oryza sativa) genotypes of semi-arid region of India - SINGH, ALOK KUMAR; DWIVEDI, D K; KUMAR, DEVENDRA; SINGH, ASHUTOSH; DIXIT, SAURABH; KHAN, N A; KUMAR, ADESH (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during rainy (kharif) seasons of 2021 and 2022 at research farm of Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya, Uttar Pradesh to find out genetic variations, trait association and path coefficient among 116 rice (Oryza sativa L.) genotypes based on grain yield and yield attributes. Variance analysis displayed extensive trait-wise variations across genotypes, indicated variability and opportunity for genetic selection of desirable traits. All the studied characters showed minimum influence of environment on the expression of trait and genetic factors. High heritability in broad sense (h2 b) and high to moderate genetic advance in per cent of the mean were recorded for all the characters. Genetic factors showed significant influence on the expression of traits, with high heritability and moderate genetic advance. Genotypic correlation with grain yield and path analysis revealed selection based on plant height, harvest index, biological yield per plant, flag leaf area, spikelet fertility, number of spikelets per panicle and seedling vigour will be more effective for increasing grain yield.